Counseling regarding healthy lifestyles in primary healthcare and the dietary practices of clients - Andrade, Karine Amorim de; Toledo, Mariana Tâmara Teixeira de; Lopes, Mariana Souza; Carmo, Glaucilene Eliane Silva do; Lopes, Aline Cristine Souza (Revista da Escola de Enfermagem da USP, 2012)
This cross-sectional study examines a counseling program on healthy lifestyles run by health care professionals to establish the adoption of healthy dietary practices by patients attending a primary health care unit. Participants in the study included 417 clients of the unit, the majority of whom were women (78.9%), with an average age of 39 years, a high incidence of excessive weight, (59.1%), important dietary inadequacies, and with a contrastingly low frequency of receiving counseling (40.8%). Clients receiving counseling displayed more appropriate consumption of candy/gum (p=0.031), softdrinks (p=0.036), salty foods (p=0.037), artificial flavorings (p=0.005) and eggs (p=0.010). Adoption of healthy dietary practices was more common among older individuals and women (p